Observations of faint galaxies with adaptive optics - Davies, R; Lehnert, M; Baker, A; Thatte, N; Renzini, A; Bonaccini, D (2003)
Encouraged by imaging of faint galaxies around bright stars using ALFA on the 3.5-m telescope at Calar Alto, we have begun a survey to identify a large number of candidate sources near bright stars. In this contribution we report the status of this survey and show our preliminary results from deep imaging around one of these stars during the early phases of CONICA and NAOS on the 8.2-m VLT. We outline the exciting prospects for this type of work in terms of number counts, morphology, and rotation curve analyses.